Effect of Work Safety and Work Healthy Towards Employee's Productivity in PT. Sisirau Aceh Tamiang - Zulkarnen Mora; Agung Suharyanto; M. Yahya (Budapest International Research and Critics University, 2020)
This study aims to determine the effect of work safety and work healthy on employee productivity in the production department at PT. Sisirau Aceh Tamiang. This research is a type of quantitative research with a sample of 45 people. The data analysis method used is multiple linear regression analysis. Hypothesis testing is done through t test, F test, and the coefficient of determination (R2). Regression equation results obtained Y = 2.255 + 0.314X1 + 0.811X2 means that the constant value of 2.255 is the value of employee productivity before being influenced by work safety and health. The work safety regression coefficient is 0.314 and is positive, meaning that if work safety is increased the employee's work productivity will increase by 0.314 with a tcount> ttable (2.333> 1.68195) and significant (0.025 <0.05). The work health regression coefficient is 0.118 and is positive, meaning that if work health is improved the employee's work productivity will increase by 0.811 with a tcount> ttable (8.063> 1.68195) and significant (0.000 <0.05). The coefficient of determination (R2) of 0.614 or 61.4%, which means the work safety and health variables influence the work productivity of employees by 61.4% and the remaining 39.6% is influenced by other variables not examined in this study.